Berbingkai Kemajemukan Budaya, Bersukma Desakalapatra: Selidik Etnografi atas Tradisi Tengger - Holifatul Hasanah; Sony Sukmawan (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This research aims to reveal the representation of multiculturalism about the complexity of the Tengger tradition. This study used a qualitative approach to the design of ethnography. The data of this research are in the form of folkloristic expressions manifested in utterances or symbolic behavior. Sources of data in this study were native speakers of Tengger. Data were collected using observation and interviews. The data obtained were then analyzed through three stages: data reduction, data presentation, and conclusions. The research findings show that multiculturalism can be represented in various Tengger tradition. Some of them are present in karo celebration performance that contains traditions of gantenan cecelukan, andon mangan, and nyandaran. Instead of these traditions, the tolerance value is also indicated in sayan tradition, such as sayan hajatan, sayan of farming, sayan of building a house, and sayan of building a place of worship. The multicultural Tengger community recognizes the concept of desakalapatra, a different custom in every Tengger region. However, by the existence of traditional support, these differences were able to be managed well. The Tengger people became more open-minded in understanding and accepting any differences between them through multiculturalism and tolerance of desakalapatra value. The solid religious tolerance in the Tengger tradition is also affected in bonding the harmony. As a result, Tengger people are always unity both culture and tradition, though they believe diversity subsistence around them.